Wood gives new life to a concrete colossus - Zorec, Maruša; Rustja, Uroš, 1983-; Golmajer, Ana.; Rijavec, Miha, 1990-; Simčič, Ana, gradbeništvo; Hovnik, Igor.; Marinič, Kristi; Senčar, Polona, 1989-; Dujič, Bruno; Jančar, Jurij; Šušteršič, Iztok (2014)
The building of the printing factory Mladinska knjiga is an existing architecture built in the 1960%s by Savin Sever, a Slovenian modernist architect. It is a structurally and materially honest load-bearing structure of concrete beams with brick infill and distinctive light openings on the roof. To revive the abandoned building, an idea of three art academies, united under one roof, was put to test, proposing a new wooden intervention to bring life into this interesting existing structure. Wooden platforms create a semipublic interior space and path connections, wooden screens form new spaces within the existing volume. Linear openings in concrete slabs allow light to descend to the lover levels. The new wooden tower with student residences, at the north of the complex, is a vertical closure of the path which leads through the building. The idea of a wooden tower is realized by stacked horizontal slabs, connected with ramps, thus creating an ambiental path. The circumference is left empty for common activities. It opens views towards the city center and the Alps.
Soavtorji: Uros Rustja, Ana Golmajer, Miha Rijavec, Ana Simcic, Igor Hovnik, Kristi Marinic, Polona Sencar, Bruno Dujic, Jurij Jancar, Iztok Sustersic.
Nasl. z nasl. zaslona.
El. članek.
Abstract.
Bibliografija: str. [8]
Keywords: lesene konstrukcije -- lesena gradnja -- večnadstropna stavba -- arhitektura -- prenova; timber upgrade -- architectural renovation -- multi-storey timber buildings